Pengembangan Bahan Ajar IPA Kelas VII SMP Materi Interaksi Makhluk Hidup Dengan Lingkungan Berbasis Kontekstual - Ayu Kristiani Handayani Gulo; Toroziduhu Waruwu (Program Studi Pendidikan Biologi - Universitas Nias, 2025)
The low quality of teaching materials used in schools is often a major obstacle in achieving student competencies in Natural Sciences subjects. This study aims to develop contextual-based science teaching materials on the material of interactions between living things and the environment for seventh grade junior high school students and to test their feasibility and effectiveness. The development was carried out by adapting the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. Data collection instruments were in the form of a feasibility assessment questionnaire for validators of material, language and presentation, and design experts, teacher and student response questionnaires, and learning outcome tests. The validation results showed a very high level of feasibility with 100% achievement from content and material experts, 97.14% from language and presentation experts, and 100% from design experts. Teacher responses to the teaching materials reached 92% with a very feasible category, while student responses in individual, small group, and field trials were 96.96%, 95%, and 87.27%, respectively, with an overall average of 91.15% in the very feasible category. The effectiveness of the teaching materials was demonstrated by the students' classical learning completion rate of 83.33%, with an average score of 78.33. In conclusion, the developed teaching materials are highly suitable and effective for use in science learning in junior high schools.